A organização do fundo Gavetas da Torre do Tombo: ponto de situação bibliográfico - Lencart, Joana (2021)
Torre do Tombo is the largest Portuguese archive. Its content, initially kept in a tower of the São Jorge castle in Lisbon, has been expanded over the centuries, despite the historical and natural incidents that have surrounded its priceless heritage, at certain times in our history. One of the broadest collections in the national archive concerns the fund Gavetas, composed of thousands of documents from the 12th century to the present. This paper intends to make a state of the art about the bibliographic production related to this collection Gavetas and its content, in order to systematise the compiled information that could be used for future historical and historiographic works.